Pengaruh Terapi Distraksi Murotal Al-Quran Terhadap Penurunan Tingkat Ansietas pada Pasien CKD yang Menjalani Hemodialisa di RSUD Toto Kabila - Yulinda Ibrahim; Firmawati Firmawati; Nur Uyun I. Biahimo; Jubaeda Abas (Lembaga Pengembangan Kinerja Dosen, 2024)
Chronic Kidney Disease (CKD) is a clinical condition characterized by an irreversible decline in kidney function to a degree that requires permanent renal replacement therapy, in the form of dialysis or kidney transplantation. One of the clinical syndromes that occurs in kidney failure is uremia. This is caused by decreased kidney function. CKD disease will cause kidney function and role to continue to decline (progressive) and cannot return (irreversible) (Sherwood, 2016). This study aims to determine the effect of Murotal Al-Qur'an distraction therapy on reducing anxiety levels in CKD patients undergoing hemodialysis at Toto Kabila Regional Hospital. This research uses a quantitative research design with a Quasy Experimental research design involving an intervention group and a control group. The population in this study were all CKD patients undergoing hemodialysis at Toto Kabila Regional Hospital. The sample in this research consisted of 15 respondents, the data collection technique was making observations and using a questionnaire sheet. Based on the results of the analysis in the treatment group, the results showed that the level of moderate anxiety was 5 respondents (62.5%), and mild anxiety was 3 respondents (37.5%). In the control group, the results showed that the level of moderate anxiety was 5 respondents (71.4%), and the results of severe anxiety were 2 respondents (28.6%). The results of statistical tests in the treatment group obtained a P-value of 0.01 and in control group 0.03 which means <0.05 so it can be concluded that Ha is accepted which means there is an effect of Murotal Al-Quran Distraction Therapy on reducing anxiety levels in CKD patients undergoing hemodialysis at Toto Kabila Regional Hospital.